2022
DOI: 10.1007/s41347-022-00267-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mobile Apps and Online Programs of Mindfulness and Self-Compassion Training in Workers: A Scoping Review

Abstract: Mindfulness and self-compassion interventions are two strategies helpful in preventing and reducing burnout and work stress. However, professionals with overburdened schedules can experience obstacles in learning and practicing these interventions, originally taught with lengthy programs. The use of digital technologies could make these interventions more accessible to workers, as studied in a recent, growing body of evidence. The evidence available is diverse in terms of interventions, designs, outcomes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…This occurrence has been frequently explored in reviews examining the effectiveness of digital mindfulness-based interventions and includes implementation obstacles, low quality of evidence, and the emergence of evidence supporting non-digital mindfulness-based interventions as more effective than their digitally delivered counterparts. This highlights a pivotal challenge for digital mental health research: balancing the rapid development and deployment of digital interventions with the rigorous, long-term evaluation necessary to validate their effectiveness and optimise their design for diverse populations [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This occurrence has been frequently explored in reviews examining the effectiveness of digital mindfulness-based interventions and includes implementation obstacles, low quality of evidence, and the emergence of evidence supporting non-digital mindfulness-based interventions as more effective than their digitally delivered counterparts. This highlights a pivotal challenge for digital mental health research: balancing the rapid development and deployment of digital interventions with the rigorous, long-term evaluation necessary to validate their effectiveness and optimise their design for diverse populations [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our participants wanted more autism-specific content and lived experience videos. Further revisions related to broader “autism-friendly” principles that have been well documented in other areas, principles such as flexibility and adaptability ( Jones, 2022 ), accessible language ( Haydon et al, 2021 ; Sarrett, 2017 ), references for additional reading, multi-modal learning opportunities ( Clouder et al, 2020 ; Davis et al, 2021 ), and the option to engage on a tablet or mobile ( Bégin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, research has shown that online programs can serve as a viable method for promoting mental health in various areas, including depression, anxiety, well-being, stress, and mindfulness. Such programs have been demonstrated to provide benefits that are comparable to face-to-face services ( Bégin et al, 2022 ; Saddichha et al, 2014 ; Sommers-Spijkerman et al, 2021 ; Spijkerman et al, 2016 ). Similarly, online self-compassion programs have demonstrated benefits, with notable increases in self-compassion, life satisfaction, and happiness and decrease in self-hatred, anxiety, stress, depression, and emotional regulation difficulties (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To summarize, the current review can help stakeholders make choices that are better aligned with the needs and realities of the target population by providing details about previous results on DIs effectiveness (see Supplementary material) and being aware of those conditions ensuring their effectiveness and their underlying working mechanisms (Table 1). Findings from previous systematic reviews highlighted the need for DIs to be designed, based on the context, in terms of the organizational preferences and target population (i.e., type of occupation) [92,93]. Realist evaluation thus takes the form of a potential approach that can be integrated into the evaluation of the DIs' effectiveness to highlight and understand which of the digital solutions worked, for whom, and under what circumstances [20].…”
Section: Strengths Limitations and Implicationsmentioning
confidence: 99%